ANALISIS LAPORAN KEUANGAN PT. TELKOM INDONESIA TBK PERIODE TAHUN 2022-2023 - Wahyu Tri Untoro; Ma’ruf Agung Kurniawan; Anom Rinumpaka; Edi Nugroho; Sri Hermuningsih (CV. ALIM'SPUBLISHING, 2025)
Financial reports in a company have a very important role. The Company's financial reports provide information about the Company's financial condition, so transparency and accountability are very important in assessing the Company's performance, especially for stakeholders. Financial reports are also used as a basis for companies in making decisions, both short and long term, for the sustainability of a company. Financial reports have an important role in performance analysis, planning and budgeting, regulatory compliance and building relationships of trust with investors and creditors. The importance of financial reports in the Company means it is necessary to carry out financial analysis. PT Telkom Indonesia Tbk Government-owned companies (State-Owned Enterprises) engaged in information technology and telecommunications services that are